The dosimetric impact of target volume delineation variation for cervical cancer radiotherapy. Issue 3 (September 2016) - Eminowicz, Gemma; Rompokos, Vasilis; Stacey, Christopher; McCormack, Mary
Abstract: Background: Cervical cancer inter-observer delineation variation has been demonstrated. This article addresses its dosimetric impact. Methods: 21 centres outlined two INTERLACE trial quality assurance test cases. A gold standard clinical target volume (GSCTV) was created from a consensus and STAPLE outline. RapidArc plans were created for all centres' planning target volumes (PTVs; PTV1 + 2). Gold standard PTVs (GSPTVs) were created for each plan by applying each centre's CTV–PTV margins to GSCTV. DVH parameters including D95% and Dmean for each PTV1 + 2 and GSPTV were compared, representing planned versus GSPTV delivered dose. PTV1 + 2 and GSPTV V95% was also calculated. Results: Reviewing all parameters, no plans achieved acceptable GSPTV coverage. GSPTV V95% ⩾ 95% was not achieved for any plan. GSPTV V95% < 90% in 15/21 (case 1) and 14/22 (case 2) and <80% in 2 plans from both cases. GSPTV V95% is on average 10–15% lower than planned and GSPTV D95% is 10–20% lower than planned. Most common GSCTV anatomical areas not receiving 95% dose were vagina, obturator and external iliac nodes and, in case 1, the superior nodal aspect. Conclusion: Cervical cancer CTV delineation variation leads to significant reductions in dose delivered to GSPTV. This highlights the ongoing importance of standardising delineation in the IMRT era.